Media representation, perception and stigmatisation of race, sexuality and HIV among young black gay and bisexual men. Issue 12 (1st December 2022) - Sallabank, Gregory; Blackburn, Natalie A.; Threats, Megan; Pulley, Deren V.; Barry, Megan C.; LeGrand, Sara; Harper, Gary W.; Bauermeister, José A.; Hightow-Weidman, Lisa B.; Muessig, Kathryn E.
Abstract: Young Black gay and bisexual men who have sex with men experience stigma related to race, gender expression, sexuality and HIV status. Stigma impacts access to HIV care and prevention as well as interactions with healthcare providers. The amplification of stigma through popular media is under-researched in the health sciences. HealthMpowerment is a mobile phone optimised intervention to reduce sexual risk and support community-building for young Black gay and bisexual men (age 18–30). We analysed Forum conversations from 48 participants, 45.8% living with HIV. Of 322 stigma-relevant conversations, 18.9% referenced the media (e.g. television, news, social media) as a source of stigma. Forum conversations covered media representations of Black gay and bisexual men, media's influence on identity, and the creation of stigma by association with media representations. Cultural messages embedded in the media may accentuate stereotypes that influence perceptions of Black gay and bisexual men and disregard intersectional identities. HealthMpowerment provided a space to challenge stigmatising representations. Participants used HealthMpowerment to garner social support and celebrate positive media representations. Interventions for young Black gay and bisexual men should consider the influential role of media and include spaces for participants to process and address stigma.